Inquiry Learning untuk Peningkatan HOTS dan Hasil Belajar IPA pada Siswa Kelas V SDN Doropayung 01 Kecamatan Juwana - Dwi Haryono; Nur Fajrie; Sri Surachmi W (Departement of Mathematics Education, 2023)
Students need Higher Order Thinking Skills (HOTS), the results of the analysis carried out by students are mastery of subject understanding. The learning atmosphere is not conducive and the lack of learning activities that support the ability to study material affects students' way of thinking, so that HOTS and student learning outcomes are not optimal, so the teacher wraps learning activities in inquiry-based learning. . This study used classroom action research which was carried out in two cycles with four main stages, namely planning, action, observation and reflection. The research subjects were 10 grade 5 students at SDN Doropayung 01, Juwana District, Pati Regency, consisting of 9 boys and 1 girl. The collected data is processed through descriptive analysis. research result showed a change in student HOTS from 30% in Pre-cycle to 60% in Cycle I and 80% in Cycle II. For science learning outcomes, coping learning increased from 40% in the Pre-Cycle to 70% in Stage I and 90% in Level II. From these results it was concluded that inquiry-based learning was proven to be able to improve HOTS and student learning outcomes, especially fifth grade students at SDN Doropayung 01